2018
DOI: 10.3390/met8030188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Porosity on Mechanical Properties and Corrosion Resistances of PM-Fabricated Porous Ti-10Mo Alloy

Abstract: Porous binary Ti-10Mo alloys were prepared using non-spherical titanium, molybdenum powders by the powder metallurgy (PM) space holder technique. Based on the three-dimensional analysis of porosity characteristics, a detailed assessment of the effects of porosity on mechanical properties and corrosion resistances in phosphate-buffered saline (PBS) was carried out. For comparison, PM-fabricated CP-Ti with 50.5% porosity sintered at 1200 • C for 2 h and dense Ti-10Mo alloy sintered at 1450 • C for 2 h (relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…This result can be strongly connected with the presence of open pores with relatively high diameter up to 25 μm ( Figure 17 ), which lead to easy penetration of the corrosive environment into the coating and cause damage. Xu et al [ 57 ] showed that the rise of porosity inevitably deteriorates the corrosion resistance, and accordingly, the corrosion rate of the porous Ti-10Mo alloy increases exponentially. In order to improve coating quality, particularly to avoid the formation of open porosity in the coating resulting from water electrolysis, and thus to enhance the electrochemical corrosion resistance of the titanium coated with zein, further research will be focused on using pulsed direct current (PDC) and alternating current (AC) electrophoretic deposition.…”
Section: Resultsmentioning
confidence: 99%
“…This result can be strongly connected with the presence of open pores with relatively high diameter up to 25 μm ( Figure 17 ), which lead to easy penetration of the corrosive environment into the coating and cause damage. Xu et al [ 57 ] showed that the rise of porosity inevitably deteriorates the corrosion resistance, and accordingly, the corrosion rate of the porous Ti-10Mo alloy increases exponentially. In order to improve coating quality, particularly to avoid the formation of open porosity in the coating resulting from water electrolysis, and thus to enhance the electrochemical corrosion resistance of the titanium coated with zein, further research will be focused on using pulsed direct current (PDC) and alternating current (AC) electrophoretic deposition.…”
Section: Resultsmentioning
confidence: 99%
“…The Ti-10Mo powder mixtures were blended with space-holder particles (ammonium hydrogen carbonate, NH 4 HCO 3 ) for 3 h, and then was cold-pressed into a cylindrical compact under 260 MPa. Finally, the isothermal sintering was carried out in the argon (Ar) protection environment at 1,300°C for 2 h. The detailed fabricating process is available in our previous study [33].…”
Section: Materials Preparation and Characterizationmentioning
confidence: 99%
“…Then the slice images were input into the Avizo software to be reconstructed. The total porosity, connected porosity and average pore sizes of the specimens were calculated by Avizo, as described in our previous study [33]. X-ray diffraction (XRD) for phase analysis was conducted with a Dmax-RB X-ray diffractometer (Cu Kα, λ=0.15406 nm, Rigaku, Tokyo, Japan).…”
Section: Materials Preparation and Characterizationmentioning
confidence: 99%
“…But these studies mainly focus on single lattice structures that cannot match the natural bones well at the strength and elastic modulus. Thus, from a design point of a view, it is imperative to design porous Ti scaffolds with different pore porosities and pore sizes, in order to match the mechanical and biological properties of natural bone [ [24] , [25] , [26] , [27] ].…”
Section: Introductionmentioning
confidence: 99%